O ensino da sistematização da assistência de enfermagem na perspectiva docente - MARQUES, Mayane Cristina Pereira (2022)
Nursing is a science based on the practice of care, thus the training of professionals who work in it transits between theoretical and practical learning. The Systematization of Nursing Care contemplates all content/action to methodologically organize the work of professionals, bringing the Nursing Process as a private activity of nurses. However, in practice, difficulties in learning it are still perceived in the nursing education process. Thus, this study aims to analyze the process of teaching the Systematization of Nursing Care in a Higher Education Institution (HEI) from the perspective of teachers. This is an analytical study with a quantitative approach carried out between January and August 2021, in 4 higher education institutions, 1 of the public network and 3 of the private education network, which offer in-class undergraduate nursing courses in the municipality of São Luís, Maranhão, Brazil. The research population was composed of 96 professors, with the sample represented by 64 nurse professors who teach specific nursing knowledge subjects in undergraduate nursing courses in the city of São Luís, according to the eligibility criteria. For data collection, we used an instrument comprising a questionnaire to be filled out by the teachers of the participating educational institutions, composed of open and closed questions about sociodemographic, educational and work data, sent through Google Forms® and analyzed by SPSS and MAXQDA®. According to the results, the teaching profile found in the study, characterized by women, with age range over 50 years, married/stable union, native of São Luís, with an average of 1.6 children, bachelor's degree, in a public institution, with 4 years of duration, the majority at a public university, who participated in PIBIC/monitoring/extension, do not have other undergraduate courses. They work at a private university and have a workload of 36 to 40 hours a week, have only one employment contract and those who have another employment contract are care nurses. According to the implementation of the Systematization of Nursing Care by teachers in their respective disciplines, most had contact with the SNA during graduation, understand the SNA and the nursing process being considered good or accurate. Regarding the subjects taught by the professors, the syllabus includes the SAE (82.8%) and (75%) uses the Theory of Basic Human Needs by Wanda de Aguiar Horta to support the SAE. According to the knowledge of professors about the teaching of Systematization of Nursing Care, they consider it necessary and applicable (95.3%) and use the standardized language classifications of Nursing (92.2%), among the most applied, the Diagnoses highlighted of Nursing at NANDA-I (53.1%), for the teaching of SAE they use some strategy (62.5%), being preferential the case study/clinical case (35.9%), they find challenges/difficulties for the teaching of SAE (67.2%) highlights the lack of implementation in health services (34.4%). The study reveals that the SAE theme is used by the professors during the nursing graduation, however, there are still difficulties in the implementation of this method in the training. It is believed that the teaching of SAE is established under the influence of some factors, among them, the teaching methodologies and strategies used by the professors. The teaching and applicability of SAE must be significant for students, as it will influence adherence and operationalization in their professional practice.